Saponins and flavonoid glycosides from the leaves of Ziziphus mauritiana Lam. native of a forest area of Ivory Coast. (June 2020) - Seri, Chardin Seri; Okpekon, Timothée Aboua; Yao-Kouassi, Philomene Akoua; Magid, Abdulmagid Alabdul; Sayagh, Charlotte; Voutquenne-Nazabadioko, Laurence
Graphical abstract: Highlights: On previously undescribed compound was identified in the leaves of Zizyphus mauritiana . The saponin possess a malonyl group in 6'''-glucose position. The structure of compound was determined by 1D and 2D NMR spectra and MS spectra. The known compounds: saponins, flavonoids and chalcone were isolated for the first time in this species. Abstract: Ziziphus mauritiana Lam (Rhamnaceae) is traditionally used in the treatment of various ailments. The aim of the present study is to identify the major compounds of the methanol extract of the leaves of Ziziphus mauritiana growing in Ivory Coast. The methanol extract of this plant was purified by combining silica gel and RP18 HPLC to give an undescribed compounds, 6'''- O -malonyl-ziziphus saponin I (1 ) along with nine known compounds from which two saponins, six flavonoids, and one chalcone derivate.The structures of these compounds were elucidated by analysis of 1D- and 2D-NMR spectroscopic data and mass spectrometry (HR-ESI-MS). A part from zizyphus saponin I (2 ), all the others compounds were isolated for the first time from the leaves of this species.